Fiscal Federalism and Demography - Helmut Seitz; Gerhard Kempkes (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2005)
The paper examines the effects of demographic change on federal, state and local governments in Germany with a focus on the expenditure side to answer the question, whether demographic change will induce vertical fiscal expenditure imbalances. We present estimates of the impact of demographic change on public spending based on a decomposition of expenditures into almost 30 categories (functions). Our results suggest that demographic change will indeed result in significant vertical expenditure imbalances between the federal and the subnational government sector as well as within the subnational government sector. In addition, the estimates show that the structure of expenditures by function has to be adjusted considerably in order to avoid deficits as demographically induced increases in expenditures in some important functions, such as pension payments, have to be counterbalanced by exploiting potential savings that arise from demographic change in other functions.
Keywords: H7; H1; J1; 330; fiscal federalism; demographic change; vertical fiscal expenditure imbalances; Finanzföderalismus; Bevölkerungsentwicklung; Öffentliche Ausgaben; Deutschland